Paralympic sport and sport-related concussion: a single case study - Chang, Y. Y.; Gemmerich, R.; Rodrigo, L.; Lausberg, H.; Arun, K. M.; Funken, J.; Helmich, I. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Sport-related concussions are common in para sport and are associated with short-term effects on cognitive functions. Due to the heterogeneous impairments in para-sport, the circumstances of handling sport-related concussion are difficult to assess. We therefore investigated in a single-case study of a Paralympic swimmer several motoric, behavioral, and neuro-cognitive parameters (before and after head collisions) that have been previously reported to be of diagnostic value in the assessment of post-concussion deficits.